1969
DOI: 10.1111/j.1464-410x.1969.tb11882.x
|View full text |Cite
|
Sign up to set email alerts
|

“Essential Hematuria” Due to a Renal Haemangioma

Abstract: ALTHOUGH renal hzmangiomas are rare, they have been recorded with increasing frequency. Thus Swan and Balme (1935) collected 35 cases from the literature, Rappoport (1945) 44 cases, Ferguson et al. (1955) 75 cases, Edward et al. (1962) 123 cases, andHagen (1963) 148 cases. Some cases have undoubtedly remained unrecorded, and others received but brief mention in larger works, for example the cases of Luck6 and Schlumberger (1957) and of Allen (1962). It is to re-emphasise that renal hzmangiomas may be the cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Thirty‐eight years later, Webb‐Johnson and Turner‐Warwick [31] described two cases of essential haematuria treated by nephrectomy in which small haemangiomas of the renal papilla were found, and concluded that, ‘Many cases of essential haematuria which have been explained in other ways may have been due to small angiomata which have been missed’. Subsequently, reports of renal haemangiomas presenting as BLH have been published occasionally [32–35], including one report of suspected bilateral renal haemangiomas [36].…”
Section: Aetiology and Pathogenesis Of Blhmentioning
confidence: 99%
“…Thirty‐eight years later, Webb‐Johnson and Turner‐Warwick [31] described two cases of essential haematuria treated by nephrectomy in which small haemangiomas of the renal papilla were found, and concluded that, ‘Many cases of essential haematuria which have been explained in other ways may have been due to small angiomata which have been missed’. Subsequently, reports of renal haemangiomas presenting as BLH have been published occasionally [32–35], including one report of suspected bilateral renal haemangiomas [36].…”
Section: Aetiology and Pathogenesis Of Blhmentioning
confidence: 99%